Removal of chemical oxygen demand from agro effluent by ZnO photocatalysis and photo‑Fenton - Wong, Soon Pang; Yahya, Marvis Sakai (Springer nature, 2019)
The direct discharge of improperly treated effluent from sago industry poses a great threat to water bodies due to the high amount of organic matter. This work investigated ZnO photocatalytic degradation under aerated and non-aerated conditions, and photo-Fenton aiming to reduce the chemical oxygen demand in sago effluent. Photolysis of sago effluent in the presence of ultraviolet irradiation and aeration resulted in 68% of the chemical oxygen demand removal. The results indicate high chemical oxygen demand reductions for different concentrations of sago effluent at 1:10, 1:100, and 1:1000 diluted with distilled water following the ZnO photocatalytic treatment under the aerated conditions. The chemical oxygen demand reductions of 90–95% and 85% were obtained using 3 g/L of ZnO, after 2 h of aerated and nonaerated photocatalytic treatments, respectively, for the sago effluent ratio of 1:1000. On the other hand, the combination of the most concentrated sago effluent at 1:10 and non-aerated ZnO photocatalytic treatment resulted in no appreciable chemical oxygen demand reduction at only 8%. The concentrations of Fe2+ (10–60 mM) and H2O2 (50–150 mM) greatly influenced the degradation rates of chemical oxygen demand. The optimum parameters of 10 mM of Fe2+ and 50 mM of H2O2 were able to reduce 97% of the chemical oxygen demand of the 1:1000 sago effluent under the photo-Fenton treatment with 2 h of ultraviolet irradiation. Thus, both ZnO photocatalysis and photo-Fenton can be applied as the possible treatment methods to reduce the chemical oxygen demand in effluent from sago processing